2007
DOI: 10.1136/jnnp.2006.103242
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 18 gene polymorphisms predict risk and outcome of Alzheimer's disease

Abstract: Background and aim: Inflammation has been extensively implicated in the pathogenesis of Alzheimer's disease (AD). Although there is evidence of a key role for cytokines in neuroinflammation processes, so far the proinflammatory cytokine interleukin (IL)-18 has not been associated with AD. The aim of this study was to investigate the impact of two polymorphisms of the human IL-18 gene promoter at positions 2607 (C/A) and 2137 (G/C) on both susceptibility to and progression of AD. Results: The results revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…The C allele of IL-18 -137 G/C has a negative correlation with AD risk in Han Chinese [34], but the CC genotype is strongly associated with accelerated cognitive decline in Caucasians [33]. Meanwhile, the C allele of IL-18 -607 and the CC genotype are associated with increased AD risk in Han Chinese and Italian Caucasian populations, respectively [33,34]. Functional analyses have revealed that the IL-18 -607 CC genotype results in significantly elevated IL-18 production by blood mononuclear cells in AD patients [35], implying that this polymorphism exacerbates AD processes via the promotion of IL-18 secretion.…”
Section: Other Pro-inflammatory Cytokinesmentioning
confidence: 95%
See 1 more Smart Citation
“…The C allele of IL-18 -137 G/C has a negative correlation with AD risk in Han Chinese [34], but the CC genotype is strongly associated with accelerated cognitive decline in Caucasians [33]. Meanwhile, the C allele of IL-18 -607 and the CC genotype are associated with increased AD risk in Han Chinese and Italian Caucasian populations, respectively [33,34]. Functional analyses have revealed that the IL-18 -607 CC genotype results in significantly elevated IL-18 production by blood mononuclear cells in AD patients [35], implying that this polymorphism exacerbates AD processes via the promotion of IL-18 secretion.…”
Section: Other Pro-inflammatory Cytokinesmentioning
confidence: 95%
“…Two SNPs in the promoter region of its gene have been reported to influence AD, -137 G/C and -607 C/A. The C allele of IL-18 -137 G/C has a negative correlation with AD risk in Han Chinese [34], but the CC genotype is strongly associated with accelerated cognitive decline in Caucasians [33]. Meanwhile, the C allele of IL-18 -607 and the CC genotype are associated with increased AD risk in Han Chinese and Italian Caucasian populations, respectively [33,34].…”
Section: Other Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Similarly, the -607C>A promoter variant disrupts the binding site for a cAMP-responsive protein. IL-18 variants have been associated with various chronic infl ammatory conditions and viral diseases, such as hepatitis B 16 and Alzheimer's disease 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies demonstrate that mutations in the IL-18 gene are also associated with the development of AD. For example, individuals carrying the CC genotype are at increased risk of developing AD [35]. Additionally, -607 C allele and -137 G allele were implicated in the risk of late-onset AD [36].…”
Section: Nlrp3 Pathway As a Target For Ad Treatmentmentioning
confidence: 99%